Geothermal field case studies that document the usefulness of models in predicting reservoir and well behavior - Lippmann, M.J. (Lawrence Berkeley Laboratory, 1989)
The geothermal industry has shown significant interest in case histories that document field production histories and demonstrate the techniques which work best in the characterization and evaluation of geothermal systems. In response to this interest, LBL has devoted a significant art of its geothermal program to the compilation and analysis of data from US and foreign fields (e.g., East Mesa, The Geysers, Susanville, and Long Valley in California; Klamath Falls in Oregon; Valles Caldera, New Mexico; Cerro Prieto and Los Azufres in Mexico; Krafla and Nesjavellir in Iceland; Larderello in Italy; Olkaria in Kenya). In each of these case studies we have been able to test and validate in the field, or against field data, the methodology and instrumentation developed under the Reservoir Technology Task of the DOE Geothermal Program, and to add to the understanding of the characteristics and processes occurring in geothermal reservoirs. Case study results of the producing Cerro Prieto and Olkaria geothermal fields are discussed in this paper. These examples were chosen because they illustrate the value of conceptual and numerical models to predict changes in reservoir conditions, reservoir processes, and well performance that accompany field exploitation, as well as to reduce the costs associated with the development and exploitation of geothermal resources. 14 refs., 6 figs.